Effect of electrochemically-driven technologies on the treatment of endocrine disruptors in synthetic and real urban wastewater. (20th April 2021) - dos Santos, Alexsandro J.; Fajardo, Ana S.; Kronka, Matheus S.; Garcia-Segura, Sergi; Lanza, Marcos R.V.
Abstract: While it remains a challenging task, having a fundamental understanding of the influence of water matrix composition is of central importance for the removal of pollutants in electrochemical treatment processes. This work studied the effect of the complexity of different water matrices on the removal of endocrine disruptors using different electrochemical advanced oxidation processes (EAOPs) based on H2 O2 electrogeneration. The study helped improve the understanding of synthetic and real urban wastewater, and the effective mechanisms for the treatment of pollutants in these effluents. The results obtained showed that, regardless of the medium applied, there was an increase in pollutants mineralization in the following order, based on the EAOPs method employed: electrochemical oxidation with H2 O2 electrogeneration (EO-H2 O2 ) < electro-Fenton (EF) < photoelectro-Fenton (PEF). Despite the slower degradation kinetics of the EO-H2 O2 process, its wider pH range makes it suitable for implementation. Aside the degradation/mineralization performance of the EO-H2 O2 process, a time-course analysis was conducted on the nitrogen and chloride-based ions in the solution investigated since their presence is vital for determining the final use of the treated effluents based on the parameters of water quality. These parameters include the established maximum concentration levels of the compounds in the water matrix allowed for human consumption or the legal limits of discharge for wastewater treatment facilities. The findings help shed light on the role of coexisting species in water matrix, since this affects the efficiency and competitiveness of EAOPs. Clearly, having detailed knowledge of the water matrix composition will help one to have a better understanding of EAOPs, and this will enable to obtain higher degradation levels in water treatment processes.